A Mini-Review on High-Penetration Renewable Integration Into a Smarter Grid - Li, Yang; Wang, Chunling; Li, Guoqing (Frontiers in Energy Research, 2020)
With the increasingly serious energy crisis and environmental pollution, the development and utilization of renewable energy resources have become an indispensable choice to ensure secure and sustainable energy supply. In recent years, the installed capacities of renewable generations such as wind power and photovoltaic are rapidly increasing, changing power generating sources of power systems from predominantly fossil power generation to high penetration of renewable generations. Unfortunately, the inherent uncertainty and variability of renewable energy sources will pose huge operational challenges in today’s power systems. At the same time, new emerging techniques, such as smart inverters, advanced communication protocols, and machine learning, provide more regulatory means available for better integration of high-penetration renewables. This paper deals with a mini-review of several emerging technologies for high-penetration renewable integration (HPRI). The main aim of this paper is the introduction of the basic concepts, principles, as well as the presentation of the main applications of these technologies in smart grids. Additionally, the challenges faced and future prospects of these technologies are also discussed. In this paper, an attempt has been made to present a comprehensive review of the research on emerging technologies in the field of renewable integration in recent years.